Principles of soil and plant water relations - Kirkham, M. B. (Academic Press, an imprint of Elsevier, 2023)
Principles of Soil and Plant Water Relations, Third Edition describes the fundamental principles of soil and water relationships in relation to water storage in soil and water uptake by plants. The book explains why it is important to know about soil-plant-water relations, with subsequent chapters providing the definition of all physical units and the SI system and dealing with the structure of water and its special properties. Final sections explain the structure of plants and the mechanisms behind their interrelationships, especially the mechanism of water uptake and water flow within plants and how to assess parameters. All chapters begin with a brief paragraph about why the topic is important and include all formulas necessary to calculate respective parameters. This third edition includes a new chapter on water relations of plants and soils in space as well as textbook problems and answers.